System analysis of metabolism in Helicobacter pylori - Correia, Daniela M. (2010)
Systems biology integrates different levels of information for understanding biological systems. The availability of the genome sequence of Helicobacter pylori has allowed the construction of a genome-scale metabolic model for this organism. In order to study the behaviour of H. pylori and understand the mechanisms associated with infection using systems biology tools and controlled cultivation conditions, fermentations in a chemically defined medium were performed and several conditions were tested. The experimental data obtained were compared with simulated data generated by the existing model. The simultaneous use of both approaches allows to correct the in silico model and, on the other hand, to rationally adjust the medium components. The improvement of the genome-scale metabolic model will allow the identification of potential targets in order to design more effective drugs for the inactivation of H. pylori.